The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-01815-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid learning curve assessment in an ex vivo training system for microincisional glaucoma surgery

Abstract: Increasing prevalence and cost of glaucoma have increased the demand for surgeons well trained in newer, microincisional surgery. These procedures occur in a highly confined space, making them difficult to learn by observation or assistance alone as is currently done. We hypothesized that our ex vivo outflow model is sensitive enough to allow computing individual learning curves to quantify progress and refine techniques. Seven trainees performed nine trabectome-mediated ab interno trabeculectomies in pig eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 59 publications
0
46
1
Order By: Relevance
“…One possible explanation for this observation was that, once the minimum TM removal required to maintain the circumferential aqueous outflow in the Schlemm's canal was established, the additional arc of TM removal became less important. Despite no continuous Schlemm's canal in the pig, there is circumferential flow as our prior studies demonstrated [13,14,16], presumably because the Schlemm's canal-like segments are connected. Limited access to angle structures, highlighted by the microsphere canalograms are sufficient to provide outflow beyond the ablated TM.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One possible explanation for this observation was that, once the minimum TM removal required to maintain the circumferential aqueous outflow in the Schlemm's canal was established, the additional arc of TM removal became less important. Despite no continuous Schlemm's canal in the pig, there is circumferential flow as our prior studies demonstrated [13,14,16], presumably because the Schlemm's canal-like segments are connected. Limited access to angle structures, highlighted by the microsphere canalograms are sufficient to provide outflow beyond the ablated TM.…”
Section: Discussionmentioning
confidence: 98%
“…Although separate studies have assessed and confirmed the efficacy of T and K, no study to date has evaluated G or performed a comprehensive comparison of the three techniques. In the past, outflow tracers were the primary method of examining flow [12][13][14][15][16] and the impact on the outflow facility was not assessed. The purpose of this study was to compare the increase of outflow facility in a porcine perfusion model by each.…”
Section: Introductionmentioning
confidence: 99%
“…The number of eyes had to be limited in this explorative study due to the intense computational requirements to process several terabytes of data in millions of confocal images. Canalogram studies of human eyes suggested a perilimbal, proximal vessel network with a density [15] similar to that of porcine eyes [16][17][18][19] . We hypothesized that an RSCM analysis of the lectin-labeled outflow tract of human eyes would match our findings in porcine eyes.…”
Section: Introductionmentioning
confidence: 81%
“…These results indicate that human eyes not only have far fewer collector channels but that their anatomy differs fundamentally by spanning several clock hours and having a 50% greater CSA. This came as a surprise because recent lower resolution canalogram studies of perilimbal outflow structures suggested a density and function of outflow vessels in human eyes [15] similar to that in porcine eyes [16][17][18][19] . The smaller number, longer course, and flatter, collapsible nature of CCs in human eyes may increase the risk of outflow failure and IOP elevation in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Increased, optic nerve-damaging intraocular pressure (IOP) in POAG was long thought to be only caused by outflow resistance at the trabecular meshwork (TM), which guards the drainage system of the eye. However, data from clinical TM ablation in thousands of patients show it fails to lower IOP to the pressure level in the recipient episcleral veins [4][5][6][7][8] . The data suggests that over half of resistance resides in the distal outflow tract (OT), downstream of the TM and Schlemm's canal (SC).…”
Section: Introductionmentioning
confidence: 99%